The role of small RNAs in resistant melon cultivar against Phelipanche aegyptiaca parasitization - Mao, Jian-Cai; Yan, Miao; Li, Jun-Hua; Yang, Jun-Yan; Wang, Hao-Jie (Frontiers in Microbiology, 2024)
Bidirectional trans-kingdom RNA silencing, a pivotal factor in plant-pathogen interactions, remains less explored in plant host-parasite dynamics. Here, using small RNA sequencing in melon root systems, we investigated miRNA expression variation in resistant and susceptible cultivars preand post-infection by the parasitic plant, broomrape. This approach revealed 979 known miRNAs and 110 novel miRNAs across 110 families. When comparing susceptible (F0) and resistant (R0) melon lines with broomrape infection (F25 and R25), 39 significantly differentially expressed miRNAs were observed in F25 vs. F0, 35 in R25 vs. R0, and 5 in R25 vs. F25. Notably, two miRNAs consistently exhibited differential expression across all comparisons, targeting genes linked to plant disease resistance. This suggests their pivotal role in melon's defense against broomrape. The target genes of these miRNAs were confirmed via degradome sequencing and validated by qRT-PCR, ensuring reliable sequencing outcomes. GO and KEGG analyses shed light on the molecular functions and pathways of these differential miRNAs. Furthermore, our study unveiled four transkingdom miRNAs, forming a foundation for exploring melon's resistance to broomrape.